A Graphical Approach for Analyses of Data Thin Non-Parametric Continuous Variable of B. dario with R: Non-Parametric Continuous Variable of B. dario with R - Paul, Shyamal Kumar; Sarker, Bhakta Supratim; Maruf, Md. Kawser Kadir; Majumdar, Priyanka Rani; Azom, Md. Golam; Saha, Debasish (Polish Journal of Natural Sciences, 2022)
Botia dario is categorized as endangered due to considerable drop in population over past two decades creates data thin condition where the nonparametric statistical methods are superior alternative approach for data drafting. Small data set necessitate graphical display reducing the chance of data compression by numerical analyses. Monthly mass and length density estimates, location, and spread were compared with R computing environment through charts and plots; proposing a graphical method for single discrete and continuous data analyses. Through graphicacy the novel method reveals the pattern for mass and length of B. dario by depicting the modes and skews of the kernel density estimates suggested wide fluctuations during pre-monsoon months; whereas the spreads and locations of boxplots draping dot-whiskers infer the Gaussian kernel by pairwise comparisons. The boxplot widths, notches of the boxplots and red dot-whiskers illustrate comprehensive variations. The novel method and suggestive narratives appeal for inclusive use excluding the limitations.